2022
DOI: 10.1002/cjp2.256
|View full text |Cite
|
Sign up to set email alerts
|

Semantic annotation for computational pathology: multidisciplinary experience and best practice recommendations

Abstract: Recent advances in whole-slide imaging (WSI) technology have led to the development of a myriad of computer vision and artificial intelligence-based diagnostic, prognostic, and predictive algorithms. Computational Pathology (CPath) offers an integrated solution to utilise information embedded in pathology WSIs beyond what can be obtained through visual assessment. For automated analysis of WSIs and validation of machine learning (ML) models, annotations at the slide, tissue, and cellular levels are required. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 47 publications
(31 reference statements)
0
15
0
Order By: Relevance
“…In the specific case, the experts involved are the biologists who select and scan the slides, the pathologists who make the annotations of the slides and the computer scientists who guide and support the annotation process ( 18 ). Indeed, the interaction between the various experts brings out critical issues to be addressed with motivated decisions to make the image acquisition and annotation process feasible and at the same time useful for possible experimentation ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the specific case, the experts involved are the biologists who select and scan the slides, the pathologists who make the annotations of the slides and the computer scientists who guide and support the annotation process ( 18 ). Indeed, the interaction between the various experts brings out critical issues to be addressed with motivated decisions to make the image acquisition and annotation process feasible and at the same time useful for possible experimentation ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…To handle very high-resolution images, a plugin for girder was created, based on OpenSlide. DSA's ease of use and excellent annotation system has led many researchers to choose it as their primary annotation system 36 , 37 or to create new datasets. 38 …”
Section: Software Platforms Specifically Designed For Digital Pathologymentioning
confidence: 99%
“…Therefore the evaluation of machine learning algorithms for digital pathology can be very delicate [180]. In [181], Wahab et al have studied, for the classification of different breast cells in H&E WSIs, the quality of annotations in terms of completeness, exhaustiveness, diversity, and agreement. They concluded that standardization of annotation protocols is necessary and proposed a new one.…”
Section: Labeled Data Quality and Quantity: How To Learn The Unexpectedmentioning
confidence: 99%